(untitled) (Materiali di Estetica. Terza serie, 2017)
The purpose of the essay is to demonstrate through the analysis of Hugo’s Le roi s’amuse how the reconciliation of opposites, which is a typical melodramatic element, is alien to the author’s poetics. In fact, the opposition of contrasts, which turns evil into good in a gradual process of formation, is not revealed in Hugo’s work as a principle of disintegration but, paradoxically, is resolved in an element of harmonious relatedness within a upper unity assured from the function of art.